Overview on grassland and farming systems in Samsun province - Acar Z.; Ayan I.; Tongel O. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
Samsun province is one of the important provinces for its high agricultural potential in Turkey. Around 45% of the province total area is suitable for cultivation. Crop production makes 81% of the total agricultural income. However, the average farm size is very small at about 4 hectares. In order to sustain the existence of small enterprises, livestock and the cultivation of forage crops with a higher added value should be developed accordingly. For this purpose, there should be more forage plants in crop rotation systems. High yielding forage crops in irrigable lands and drought-resistant, ever green plants in summer period in non-irrigable sloping lands are necessary to provide the animal feed chain with high energy resources.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)